Give Me Benefit And Data! Exploring the Impact of Advertising on Eye Health Product Purchase Intention (The Journal of Medicine, Humanity and Media, 2024)
With the implementation of the "Healthy China Strategy", the increasing awareness of health among residents and the spread of health anxiety to younger generations, the health product market is experiencing rapid growth. Eye health care products have achieved significant growth, and persuasive strategies of health product advertising and the consumption of health products by younger age groups have become issues of concern. This study explores the effects of framework and evidence type of eye health care product advertising on purchase intention and the mediation effect of perceived risk and benefit and the moderating effect of psychological distance on young consumers. The study used online experimental methods to conduct a 2 (framework: benefit versus loss) x 2 (evidence type: statistics versus narrative) grouped experiment. The study found that compared to loss frameworks and narrative evidence, benefit frameworks and statistical evidence are more likely to promote the purchase intention of young consumers. Perceived benefits mediate the effect of evidence type on purchase intention, and psychological distance moderates the effect of framework on purchase intention. These findings enrich the application of framework and its impact on health beliefs and behaviors and provide a reference basis for building an advertising framework that can better influence consumer health behavior and purchase intention.
Keywords: Health product advertising; Framework; Evidence type; Purchase intention